Drainage water reuse in the Nile Delta of Egypt: Fitting density functions and assessing temporal trends. (24th April 2020) - Shaban, M.
Abstract: This study attempts to investigate the variability in the current drainage water reuse pattern in terms of discharges (DWR (MCM) and their corresponding salinities (DWR (TDS mg l¯¹)) recorded since 1984 in the Nile Delta regions (Case I). In addition, the expected future DWR (DWR_E) patterns were simulated, taking into account the expected future reuse expansion projects (Case II). For Case I, basic descriptive statistics as well as non‐parametric assessment for monotonous trends were employed to characterize the structure of the DWR discharge and salinity data sets. Also, best probability density functions (PDFs) were fitted as smoothed adaptations to predict the occurrence probability in a certain interval. These analyses were repeated (excluding trend assessment) for aggregated discharge and salinity data simulating the possible future DWR patterns (Case II). The results indicate that DWR discharge and salinity series had increasing trends except the DWR salinity measured in the Western Nile Delta region that showed an insignificant decreasing trend. The results also show that there is a potential for increasing the mean DWR discharges up to 101, 32.6 and 282% for the Eastern, Middle and Western Delta regions, respectively. This will be accompanied with DWR salinity increases up to 39.5, 11.4 and 46.1%, respectively. © 2020 John Wiley & Sons, Ltd. Résumé: Cette étude tente d'étudier la variabilité du schéma actuel de réutilisation des eaux de drainage en termes de rejets (DWR (MCM) et leurs salinités correspondantes (DWR (TDS mg l¯¹)) enregistrées depuis 1984 dans les régions du delta du Nil (cas I). De plus, les futurs modèles DWR attendus (DWR_E) ont été simulés en tenant compte des futurs projets d'expansion de réutilisation prévus (cas II). Pour cas I, des statistiques descriptives de base ainsi qu'une évaluation non paramétrique des tendances monotones ont été utilisées pour caractériser la structure des ensembles de données de débit et de salinité DWR. De plus, les meilleures fonctions de densité de probabilité (PDF) ont été ajustées en tant qu'adaptations lissées pour prédire la probabilité d'occurrence dans un certain intervalle. Ces analyses ont été répétées (à l'exclusion de l'évaluation des tendances) pour les données agrégées de débit et de salinité simulant les futurs modèles DWR possibles (cas II). Les résultats indiquent que les séries de débit et de salinité DWR avaient des tendances à la hausse, sauf la salinité DWR mesurée dans la région du delta du Nil occidental, qui montrait une tendance à la baisse peu significative. Les résultats montrent également qu'il existe un potentiel d'augmentation des rejets moyens de DWR jusqu'à 101, 32.6 et 282% pour les régions du delta oriental, moyen et occidental, respectivement. Cela s'accompagnera d'une augmentation de la salinité DWR jusqu'à 39.5, 11.4 et 46.1, respectivement. © 2020 John Wiley & Sons, Ltd.